Development of RME-Based E-Modules with Ethnomathematics Integration to Improve Graphic to Symbolic Transformation Skills in Junior High School Mathematics - Putri, Alfiani Athma Athma; Wajid, Abdul; Irawan, Ruli; Usmiyatun, Usmiyatun (AL-ISHLAH: Jurnal Pendidikan, 2026)
Students often experience difficulty translating graphic representations into symbolic mathematical forms, indicating the need for learning resources that connect abstract concepts with meaningful contexts. This study aimed to develop an e-module based on Realistic Mathematics Education (RME) integrated with the ethnomathematics of rumah betang to improve students’ ability to transform graphic representations into symbolic representations. This research employed a development design using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. The feasibility of the e-module was evaluated by material and media experts. Its practicality was examined through a small-group trial, while its effectiveness was tested in a large-group implementation using pretest and posttest scores. Expert validation indicated that the e-module was categorized as “very feasible” in terms of material and media quality. The small-group trial showed that the e-module was “practical” for use in mathematics learning. In the large-group trial, students’ average score increased from 63.92 on the pretest to 84.72 on the posttest. The N-gain score was 0.59, indicating a medium improvement, with an effectiveness percentage of 58.81%, categorized as moderate. The findings suggest that the RME-based e-module integrated with rumah betang ethnomathematics is feasible, practical, and moderately effective in supporting students’ representation ability. The e-module can be used by teachers as an innovative culturally contextualized learning medium and by students for independent or collaborative learning. Further studies may examine its effects on other mathematical abilities, such as critical thinking and problem solving.